Genetic Diseases (Literature Review) - Ajimuratova Venera Bakhitjanova (Genius Journals, 2024)
Increased knowledge of genomics over the past two decades has made it increasingly clear that traditional categories of genetic diseases define only those conditions in which the genetic component is most prominent, whereas in fact diseases can be grouped according to a variety of traits representing different combinations of genes and environmental factors. Knowledge of genomics that can benefit humans is only just emerging, and it is anticipated that genomics will "make a significant contribution to public health" in the future
Keywords: Chromosomal abnormalities; diagnosis; prenatal diagnosis